The origin of ultrafast outflows in AGN: Monte Carlo simulations of the wind in PDS 456 - Hagino, Kouichi; Odaka, Hirokazu; Done, Chris; Gandhi, Poshak; Watanabe, Shin; Sako, Masao; Takahashi, Tadayuki (Monthly notices of the Royal Astronomical Society, 2015)
Ultrafast outflows (UFOs) are seen in many AGN, giving a possible mode for AGN feedback on to the host galaxy. However, the mechanism(s) for the launch and acceleration of these outflows are currently unknown, with UV line driving apparently strongly disfavoured as the material along the line of sight is so highly ionized that it has no UV transitions. We revisit this issue using the Suzaku X-ray data from PDS 456, an AGN with the most powerful UFO seen in the local Universe. We explore conditions in the wind by developing a new 3D Monte Carlo code for radiation transport. The code only handles highly ionized ions, but the data show the ionization state of the wind is high enough that this is appropriate, and this restriction makes it fast enough to explore parameter space. We reproduce the results of earlier work, confirming that the mass-loss rate in the wind is around 30 per cent of the inferred inflow rate through the outer disc. We show for the first time that UV line driving is likely to be a major contribution to the wind acceleration. The mass-loss rate in the wind matches that predicted from a purely line driven system, and this UV absorption can take place out of the line of sight. Continuum driving should also play a role as the source is close to Eddington. This predicts that the most extreme outflows will be produced from the highest mass accretion rate flows on to high-mass black holes, as observed.